2004
DOI: 10.1111/j.0013-9580.2004.41403.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual Function in Infants with West Syndrome: Correlation with EEG Patterns

Abstract: Summary:Purpose: Several studies have reported behavioral and electrophysiological evidence of visual impairment during the active stage of West syndrome. The underlying mechanisms are, however, poorly understood, and little has been reported about the correlation between visual impairment, EEG patterns, and brain lesions. The aim of the study was to assess visual function at the onset of spasm and 2 months thereafter and relate visual findings to brain lesions and EEG features.Methods: Twenty-five infants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 22 publications
4
23
1
Order By: Relevance
“…The presence of early epilepsy was in contrast always associated with severe visual abnormalities. In keeping with previous recent studies suggesting that West syndrome and early severe epilepsy can affect visual behaviour 16 we also found that early epilepsy was associated not only with abnormal visual findings at the time of onset of the seizures but also with a reduced chance of recovery. While the three infants with shunt and venous infarct who did not have epilepsy showed an improvement of behavioural visual tests after the first months, all the four patients with early epilepsy did not show any recovery.…”
Section: Discussionsupporting
confidence: 92%
“…The presence of early epilepsy was in contrast always associated with severe visual abnormalities. In keeping with previous recent studies suggesting that West syndrome and early severe epilepsy can affect visual behaviour 16 we also found that early epilepsy was associated not only with abnormal visual findings at the time of onset of the seizures but also with a reduced chance of recovery. While the three infants with shunt and venous infarct who did not have epilepsy showed an improvement of behavioural visual tests after the first months, all the four patients with early epilepsy did not show any recovery.…”
Section: Discussionsupporting
confidence: 92%
“…However, the lower apparent prevalence in these two studies may merely reflect the difficulty in assessing visual field loss in children. The situation is also complicated by possible underlying ocular and visual abnormalities in children with infantile spasms, [19,20] a frequent indication for vigabatrin therapy. However, no study has been undertaken that directly compares the frequency of VAVFL between children and adults.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired eye-hand coordination was found to be deficient when infants were evaluated, even in idiopathic patients who appear to be functioning normally otherwise (Rando et al 2005). Impaired visual functioning involving acuity, ocular motility, visual field, visual attention, and visual scanning skills have been found in several studies with infants (Guzzetta et al 2002;Rando et al 2004). Guzzetta (2006) reported an associated deficit in auditory attention, and visual and auditory functions were both correlated with cognitive competence on the Griffith Scales of Infant Development.…”
Section: West Syndromementioning
confidence: 93%